Thermal and Photolytic Transformation of NHC–B, N‐Heterocycles: Controlled Generation of Blue Fluorescent 1, 3‐Azaborinine Derivatives and 1H‐Imidazo[1, 2‐a]indoles by External Stimuli. Issue 40 (19th August 2015) - McDonald, Sean M.; Mellerup, Soren K.; Peng, Jinbao; Yang, Dengtao; Li, Quan‐Song; Wang, Suning
Abstract NHC–B, N‐heterocyclic compounds have been found to act as convenient precursors for obtaining either 1, 3‐azaborinine or 1H‐imidazo[1, 2‐a]indole derivatives, which are two different and rare classes of compounds. The formation of these two classes of compounds from the NHC–B, N‐heterocycles is highly selective depending on the external stimuli employed, and the resulting products have been studied for their interesting chemical and photophysical properties. The mechanism and possible reaction pathways of the unusual transformation are established by computational studies.